The structure of the box C/D enzyme reveals regulation of RNA methylation - Lapinaitė, Audronė; Simon, Bernd; Skjaerven, Lars; Rakwalska-Bange, Magdalena; Gabel, Frank; Carlomagno, Teresa (Nature, 2013)
Post-transcriptional modifications are essential to the cell life cycle, as they affect both pre-ribosomal RNA processing and ribosome assembly. The box C/D ribonucleoprotein enzyme that methylates ribosomal RNA at the 2′-O-ribose uses a multitude of guide RNAs as templates for the recognition of rRNA target sites. Two methylation guide sequences are combined on each guide RNA, the significance of which has remained unclear. Here we use a powerful combination of NMR spectroscopy and small-angle neutron scattering to solve the structure of the 390 kDa archaeal RNP enzyme bound to substrate RNA. We show that the two methylation guide sequences are located in different environments in the complex and that the methylation of physiological substrates targeted by the same guide RNA occurs sequentially. This structure provides a means for differential control of methylation levels at the two sites and at the same time offers an unexpected regulatory mechanism for rRNA folding.
Gesehen am 12.10.2021